2010
DOI: 10.21236/ada515369
|View full text |Cite
|
Sign up to set email alerts
|

Performance of SONY 18650-HC Lithium-Ion Cells for Various Cycling Rates

Abstract: REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Upon overcharge, lithium that has not moved to occupy the intercalation site in the anode is deposited on the surface of the anode [36]. This formation is termed lithium plating.…”
Section: Thermal Runaway Behaviormentioning
confidence: 99%
“…Upon overcharge, lithium that has not moved to occupy the intercalation site in the anode is deposited on the surface of the anode [36]. This formation is termed lithium plating.…”
Section: Thermal Runaway Behaviormentioning
confidence: 99%
“…The latter showed evidence of lithium plating, with large salts and oxides deposits throughout the surface, especially near to edges and surface irregularities, thus according to Zimmermann and Quinzio. 25 Some dendrites starts were identified too, which grew from anode surface and threatened separator integrity. EDS analysis confirmed qualitative composition of electrodes as well as plated deposits.…”
Section: Hmentioning
confidence: 99%
“…More gaseous by-product would be formed which stretches and damages the surface film. While the percentage of capacity loss does not scale linearly with the discharge current, experimental results have clearly shown that higher current above 1C leads to much faster capacity loss during cycling [13,14]. In order to complete the investigation on the optimal current for discharging, this study investigates the low current degradation mechanisms by modeling the cumulative effect of these side reactions.…”
Section: Introductionmentioning
confidence: 99%